2018
DOI: 10.1002/adom.201701380
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control of the Topological Transition in Metal/Photoemissive‐Blend Metamaterials

Abstract: intriguing opportunity. HMMs are uniaxial structures manifesting a hyperbolic dispersion relation whose application range spans from hyperlensing to extreme biosensing. [13][14][15][16][17][18][19][20][21][22][23][24] In order to describe their optical constants, it is convenient to homogenize the dielectric permittivity of HMMs by using the effective medium theory (EMT). If the dimensions of the fundamental components of the HMM, that in our case consists of alternated metal/dielectric layer pairs, are chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, for fewlayer metal/insulator stacks, the origin and nature of the ENZ resonances are still under investigation [5,7,39]. For example, the effective medium theory fails to predict their effective permittivity [5,40,41], and it can be debated if the ENZ resonances are photonic or plasmonic or if classical or quantum mechanical models should be applied [7]. In a recent work, we demonstrated that MIM cavities can be seen as a double barrier quantum well and that the ENZ cavity modes can be treated as the resonant tunneling of photons [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, for fewlayer metal/insulator stacks, the origin and nature of the ENZ resonances are still under investigation [5,7,39]. For example, the effective medium theory fails to predict their effective permittivity [5,40,41], and it can be debated if the ENZ resonances are photonic or plasmonic or if classical or quantum mechanical models should be applied [7]. In a recent work, we demonstrated that MIM cavities can be seen as a double barrier quantum well and that the ENZ cavity modes can be treated as the resonant tunneling of photons [7].…”
Section: Introductionmentioning
confidence: 99%
“…Such high refractive index sensitivity is attributed to strong near‐field enhancement of surface plasmon waves on the interface of a metal and a hyperbolic chiral‐sculptured thin film. Besides biosensing application, temperature sensor is also designed based on HMMs using hygroscopic dielectric blend . This dielectric blend consists of a polymer, a sol–gel unsintered TiO 2 , and an organic dye.…”
Section: D Bulk Hyperbolic Metamaterialsmentioning
confidence: 99%
“…Compared with other optical metamaterials, like chiral and split ring resonator–based metamaterials, HMMs have advantages of relative ease of fabrication at optical frequencies, broadband nonresonant and 3D bulk responses, and flexible wavelength tunability. As a result, HMMs have attracted widespread interest and become a good multifunctional platform for many exotic applications, such as optical negative refraction and light beam steering, subdiffraction‐limited imaging and nanolithography, spontaneous and thermal emission engineering, ultrasensitive optical, biological, and chemical sensing, omnidirectional and broadband optical absorption …”
Section: Introductionmentioning
confidence: 99%